CEO overconfidence in the U.S. banking industry - Liu, Liang (2017)
The financial crisis that started in 2008 has had a significant impact around the global. In the US alone, it is estimated that approximately $14 trillion of wealth has been lost (Luhby 2009). A considerable body of literature has focused on the role of excessive risk-taking by banks in the years preceding the crisis (Laeven & Levine 2009; Fouque & Langsam 2013; Weiß et al. 2014). We still have limited knowledge, however, about why some financial institutions take more excessive risks than others, despite the fact that these financial institutions are subject to the same financial regulations and macroeconomic environment (Lo 2011; Barone-Adesi et al. 2013; Xiong 2013). This concern about excessive risk taking by banks has encouraged scholars to study the possible causes. A common argument is that the subprime and financial crisis was not due to regulatory failure, but psychological failure (Shefrin 2009; Barberis 2011). If this is the case, it would suggest that any explanation of the causes of the recent banking crisis that focuses only on bank characteristics, failure of financial regulations and market discipline may be incomplete.